Urinary Kallidinogenase plus rt-PA Intravenous Thrombolysis for Acute Ischemic Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (17th May 2022) - Wu, Jing; Wu, Jiang; Wang, Le; Liu, Jinmin
Abstract : Purpose . This research is aimed at systematically assessing the safety and effectiveness of intravenous thrombolysis (IVT) with rt-PA plus human urinary kallidinogenase (HUK) for acute ischemic stroke (AIS). Methods . The data were obtained through rigorous searching of both domestic and foreign databases from inception to 2021.7.1. Randomized controlled trials (RCTs) were included for the comparison of the efficacy of IVT plus HUK. The Cochrane risk of bias (RoB) tool and Review Manager software 5.3 were responsible for RoB assessment and statistical analyses, respectively. Results . A total of 18 articles were retrieved, including 2676 AIS patients treated with IVT within the time window. The control group used standardized rt-PA IVT, and the test group added HUK. After 14 days of combined application of HUK, the National Institute of Health Stroke Scale (NIHSS) score was significantly better in moderate stroke patients using the combination treatment versus those with IVT alone (mean   difference   MD = − 3.13 ; 95% confidence intervals (CI): -3.40, -2.86; P < 0.00001 ); the NIHSS score was also statistically in severe stroke patients with combined treatment than in those with IVT alone, but the degree of recovery of patients varied greatly. After 90 days of treatment, the NIHSS (MD = − 1.93 ; 95% CI: -2.51, -1.34; P < 0.00001 ) and Barthel index (BI) scores (MD = 22.23 ; 95% CI: 18.96, 25.49; P < 0.00001 ) of patients plus HUK were significantly better than those of patients with IVT alone, with fewer adverse events during treatment (Relative   Risk   RR = 0.66 ; 95% CI: 0.47, 0.92; P = 0.02 ). Conclusions . For AIS patients with IVT within the time window, HUK plus rt-PA IVT could significantly improve the neurological function recovery after 14 days and the quality of life after 90 days and reduce the adverse reactions of IVT. This trial is registered with CRD42021226975 .